Unexpected encounter of Pandoraea species in urine sample: A case report - Parajuli, Kshitiz; Neupane, Aron; Khatiwada, Aakash; Singh, Randhir Kumar (Journal of Karnali Academy of Health Sciences, 2026)
Isolation of Pandoraea species from urine specimen in Nepal is a rare microbiological discovery. A 21-year-old female presented with episiotomy site pain and lower-limb edema five days postpartum. The urine culture grew non-lactose-fermenting, Gram-negative bacilli, which, on VITEK-2 analysis, were identified as Pandoraea species with a probability of 94%. The extensive antimicrobial susceptibility profile obtained showed susceptibility to very few antimicrobials. The microorganism’s resistance to multiple antibiotics indicates potential issues with proper microbial identification. To our knowledge, this is the first isolation of Pandoraea species from Nepal.